The Effect of Polyphenol Supplementation on Recovery Following High-Intensity Interval Training - Fałczyńska, Aleksandra; Wawrzyniak, Maria; Linke, Julia; Szamałek, Karolina; Kozłowska, Dominika; Boral, Wiktoria; Dróżdż, Marek; Marzec, Wiktoria; Kopeć, Stanisław (Journal of Education, Health and Sport, 2026)
Polyphenols are a diverse group of plant-derived compounds. As a part of the human diet, they have a broad spectrum of biological activity, including antioxidant, anti-inflammatory, and immunomodulatory properties through multiple metabolic pathways. High-intensity interval training (HIIT) exercise, although widely used to improve physical performance, is associated with causing substantial metabolic and oxidative stress, inflammation, hormonal imbalance, and muscle damage. Some studies indicate that polyphenol intake may inhibit reactive oxygen species formation, modulate cytokine release, lower lipid peroxidation and damage of deoxyribonucleic acid, and improve markers of muscle recovery, potentially accelerating recovery after HIIT. However, other research contradicts the positive impact of polyphenol supplementation on recovery or performance.